An Assessment of The Bibliofile Cataloguing Software at The University of Education, Winneba Library - Arkorful, Mary A. (Ghana Library Journal, 2004)
Through financial support from the World Bank, the Bibliofile, a cataloguing software was purchased for the University of Education, Winneba Library. Five years after its installation, this paper evaluates the Bibliofile in the context of its cataloguing facilities, assesses its impact on the cataloguing service and information retrieval in the library as a whole.